DEVELOPMENT AND VALIDATION LEARNING MATERIALS OF WAVES CONTAINS HOLY AL-QURAN VALUES - Masitah, Fatma Nuril; Rosana, Dadan (Unnes Science Education Journal, 2019)
The research aims to develop learning materials. In addition, the research also tested the validation of physics materials learning using holy Alquran. The preparation of learning materials contains holy Quran values become very important to use when learning school. Learning materials that have been fitted Alquran values can help improve the insights of science as well as add value to the spiritual attitude of learners. Learning materials are also expected to invite learners to more easily understand a material through contemplation. For example, by incorporating the results of the interpretation of some verses of the Qur'an to wave material class 11. Research on learning materials contains holy Alquran values using the approach to research and development. Further learning materials are validated by experts in their field to be used as guidelines revision of materials. Expert lecturers and practitioners considered viable materials used as learning materials categorized very well with the value Ëƒ 3,00. In addition, the materials also received excellent response 87.5% of the learners.